Metabolic Reprogramming in Prostate Cancer: The Roles of HOXB13 and FASN in Tumor Progression and Therapy - Saeed, Faisal; Harik, Lara (Serican Journal of Medicine, 2025)
Metabolic reprogramming, particularly lipid metabolism, is a hallmark of cancer progression and a critical vulnerability in prostate cancer (PCa). Two pivotal studies, one by Lu et al. and the other by Dairo et al., have illuminated the roles of HOXB13, a transcriptional regulator, and fatty acid synthase (FASN), a key enzyme in lipid biosynthesis, in the metabolic dysregulation of PCa. The Lu et al. study highlights HOXB13’s role in androgen receptor (AR)-independent PCa, where it regulates lipid metabolism via epigenetic mechanisms involving histone deacetylase HDAC3. A G84E mutation in HOXB13 disrupts this regulation, leading to increased lipid synthesis and a pro-metastatic phenotype. The Dairo et al. study demonstrates that FASN hypomethylation, coupled with increased expression, drives lipid biosynthesis critical for tumor growth. Both studies establish a link between HOXB13 mutations and FASN dysregulation, underscoring their interplay in PCa biology. Therapeutically, pharmacological inhibition of FASN mitigates the aggressive features of HOXB13-deficient or mutant PCa, highlighting lipid metabolism as a promising target. Despite their strengths, including robust methodologies, limitations include reliance on preclinical models and the need for broader patient diversity. These studies collectively emphasize the potential of metabolic and epigenetic interventions for precision medicine in PCa, paving the way for novel therapies targeting lipid metabolism in patients with specific genetic and epigenetic profiles.